Effect of audio and visual distraction on patients undergoing colonoscopy: a randomized controlled study - De Silva, A. P.; Niriella, M. A.; Nandamuni, Y.; Nanayakkara, S. D.; Perera, K. R. P.; Kodisinghe, S. K.; Subasinghe, K. C. E.; Pathmeswaran, A.; de Silva, H. J. (Endoscopy International Open, 2016)
Background and study aims: Colonoscopy can cause anxiety and discomfort in patients. Sedation and analgesia as premedication can lead to complications in the elderly and those with comorbidities. This has led to an interest in the use of audio-visual distraction during the colonoscopy. We compared the effects of audio (AD) versus visual distraction (VD) in reducing discomfort and the need for sedation during colonoscopy.Patients and methods: Consecutive patients undergoing colonoscopy were randomized into three groups: one group was allowed to listen to the music of their choice (AD), the second group was allowed to watch a movie of their choice (VD), and the third group was not allowed either distraction during colonoscopy and acted as a control (C). Patient controlled analgesia and sedation were administered to all three groups. We used 25 mg of pethidine in 5-mg aliquots and 2.5 mg of midazolam in 0.5-mg aliquots. All patients were assessed for perceived pain and willingness to repeat the procedure. Number of “top-ups” of sedation and total dose of pethidine and midazolam were noted. Patient cooperation and ease of procedure were assessed by the colonoscopist.Results: In total, 200 patients were recruited [AD, n = 66 (32 males, median age 57 years); VD, n = 67 (43 males, median age 58 years); C, n = 67 (35 males, median age 59 years)]. The AD group had significantly less pain (P = 0.001), better patient cooperation (P = 0.001) and willingness to undergo a repeat procedure (P = 0.024) compared with VD and C groups.Conclusions: AD reduces pain and discomfort, improves patient cooperation and willingness to undergo a repeat procedure, and seems a useful, simple adjunct to low dose sedation during colonoscopy.Study registration: SLCTR/2014/031.